2014
DOI: 10.1016/j.cub.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Energetics: Actin and Myosin Abstain from ATP during Starvation

Abstract: Energy is required for all cellular functions and diverse mechanisms allow the cell to overcome acute energy starvation. A new study reveals that starved cells inhibit type V myosins and actin depolymerization, measures that may conserve energy while temporarily retaining cell polarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Importantly, the model distinguishes between actin cortex components that support energy starvation and those that require energy consumption. Although actin polymerization is a major consumer of ATP, cells account for well-conserved mechanisms to stabilize the actin cytoskeleton in absence of ATP 45,49 . This is consistent with a quiescent state of the cell, in which the actin cortex adopts a minimal but stable conformation.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the model distinguishes between actin cortex components that support energy starvation and those that require energy consumption. Although actin polymerization is a major consumer of ATP, cells account for well-conserved mechanisms to stabilize the actin cytoskeleton in absence of ATP 45,49 . This is consistent with a quiescent state of the cell, in which the actin cortex adopts a minimal but stable conformation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that glucose starvation occurs during many diseases, such as hypoglycemia, heart attack, or highly proliferative cancers. 29 To investigate the ability of the nanoaptasensor to monitor ATP fluctuation at the subcellular level under glucose starvation, glucose was removed from the cell culture medium. Then, the nanoaptasensor was inserted into different regions of single cells to incubate for 2 min, and the electrochemical detections were performed in vivo.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When the glucose starvation lasted for 40 min, the metabolic activity of cells within a dormant state maintains the viability of cells. 29 After ATP detection during the starvation process, the cell viability of penetrated cells was further verified by staining with Calcein-AM. It is surprisingly found that some of cells exhibit bright green fluorescence emissions in Figure 3B even when they underwent eight insertions (including four insertions into the nucleus and four insertions into the cytoplasm in the course of glucose starvation), indicating they are living.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations